Does pelvic radiation increase rectal cancer incidence? – A systematic review and meta-analysis. (July 2018) - Rombouts, A.J.M.; Hugen, N.; van Beek, J.J.P.; Poortmans, P.M.P.; de Wilt, J.H.W.; Nagtegaal, I.D.
Highlights: There is an increased risk for rectal cancer following radiation to a pelvic organ. The incidence of rectal cancer following pelvic radiation increases with time. In the literature, there is little to no uniformity in latency period thresholds. Abstract: Background: One of the late complications associated with radiation therapy (RT) is a possible increased risk of second cancer. In this systematic review, we analysed the incidence of rectal cancer following primary pelvic cancer irradiation. Methods: A literature search was conducted using the PubMed and EMBASE libraries. Original articles that reported on secondary rectal cancer after previous RT for a primary pelvic cancer were included. Sensitivity analyses were performed by correcting for low number of events, high risk of bias, and outlying results. Results: A total of 5171 citations were identified during the literature search, 23 studies were included in the meta-analyses after screening. A pooled analysis, irrespective of primary tumour location, showed an increased risk for rectal cancer following RT (N = 403.243) compared with non-irradiated patients (N = 615.530) with a relative risk (RR) of 1.43 (95% confidence interval [CI] 1.18–1.72). Organ specific meta-analysis showed an increased risk for rectal cancer after RT for prostate (RR 1.36, 95%CI 1.10–1.67) and cervical cancer (RR 1.61, 95% CI 1.10–2.35). No relation was seen in ovarian cancer patients. The modality of RT did not influence the incidence of rectal cancer. Conclusions: This review demonstrates an increased risk for second primary rectal cancer in patients who received RT to the pelvic region. This increased risk was modest and could not be confirmed for all primary pelvic cancer sites. The present study does not provide data to change guidelines for surveillance for rectal cancer in previously irradiated patients.